The Last Word on the Wage Curve? - Peter Nijkamp; Jacques Poot (Tinbergen Institute, 2002)
In the last decade we have seen extensive international research on the extent to which wages of individuals respond to changing local labour market conditions. For many countries and periods, an inverse relationship between wages and unemployment rates has been found. Following Blanchflower and Oswald (1990), this relationship is referred to as the wage curve. The elasticity of this wage curve has been reported to be so similar across studies, at a level of about -0.1, that Card (1995) called it an empirical law of economics. However, there is considerable heterogeneity among wage curve studies. This paper carries out modern meta-analytic techniques on a sample of 208 elasticities derived from the literature to uncover the reasons for the differences in empirical results across studies. It is found that the wage curve is a robust empirical phenomenon, but there is also clear evidence of downward publication bias. In addition, many reported t statistics are biased upwards due to the use of aggregate unemployment rates and other labour market characteristics for groups. A maximum likelihood method and a trimming procedure are used to correct for these biases. Both methods give similar results for our sample. An unbiased estimate of the wage curve elasticity is about -0.07.
Keywords: C12; C13; J31; R23; 330; wage curve; meta-analysis; publication bias; Lohnbildung; Arbeitslosigkeit; Theorie